The Social Construction of the Rebo Wekasan Ritual in Building Collective Trust in the Karundang Tengah Community to Increase Social Resilience During the COVID-19 Pandemic - Putri, Liza Diniarizky; Parani, Rizaldi; Malik, Abdul (Institute of Research and Community Outreach - Petra Christian University, 2023)
The Rebo Wekasan ritual which has become a tradition in various regions of the archipelago aims to seek safety from the arrival of danger and is a form of guarding or rejecting reinforcements and asking to be protected from harm. The purpose of this study was to investigate how Rebo Wekasan as a ritual in building the collective trust of the Karundang community as an effort to grow social resilience in a pandemic. This study uses social construction theory. The approach used is qualitative by interviewing the leader of the neighborhood association, a religious leader, the daughter of a traditional leader, and one citizen. The main results of this research, obtained through thematic analysis, are first, while most people construct the Rebo Wekasan ritual as an effort to reject reinforcements and maintain tradition, some see it as simply an attempt to reduce stress due to the pandemic; second, while these constructions are different, the three of them together can encourage collective resilience in the form of stress reduction; third, related to mechanisms, three ways allow construction to lead to collective resilience, namely through traditional mechanisms, functional mechanisms, and pragmatic mechanisms. Based on these results, it can be concluded that the community's construction of the Rebo Wekasan ritual led to several mechanisms, resulting in community resilience in facing the pandemic.